A materialidade da cor: algumas concepções de pintura contemporânea brasileira - Sanovicz, Monica Soares Tinoco [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
A tese discute as manifestações cromáticas elaboradas por alguns artistas contemporâneos, brasileiros e estrangeiros, que exploram as potencialidades da cor no seu caráter físico, concreto e material, evidenciando sua ambiguidade e propiciando inovações nos objetos pictóricos. O estudo também apresenta a produção pictórica pessoal, realizada no período de 2006 a 2019.

The thesis discusses the chromatic manifestations elaborated by some contemporary artists, Brazilian and foreign, who explore the potential of color in its physical, concrete and material character, showing its ambiguity and providing innovations in pictorial objects. The study also presents personal pictorial production, carried out in the period from 2006 to 2019.
The materiality of color: some conceptions of contemporary Brazilian painting
Keywords: Pintura; Cor; Materialidade da cor; Pintura brasileira; Painting; Color; Color materiality; Brazilian painting; Contemporary painting; Pintura contemporânea